Fournier’s Gangrene - Alfonsus Mario Eri Surya Djaya (Cermin Dunia Kedokteran, 2018)
Fournier’s gangrene merupakan suatu fasiitis nekrotikans perianal, perineal, serta genital yang progresif dan fatal. Diagnosis bisa ditegakkan dengan gambaran klinis. Prinsip utama penanganan adalah resusitasi adekuat, pemberian antibiotik parenteral, serta tindakan debridement. Diversi urin ataupun fekal, terapi hiperbarik, dan operasi rekonstruksi memperbaiki hasil akhir. Walau penanganan tepat, angka mortalitas cukup tinggi. Beberapa metode prediksi mortalitas meliputi Laboratory Risk Indicator for Necrotizing Fasciitis Score (LRINEC) dan Fournier Gangrene Severity Index (FGSI). Dilaporkan kasus dan penanganan Fournier’s gangrene di rumah sakit tipe C di Jember, Jawa Timur.   Fournier’s gangrene is a progressive and fatal necrotizing fasciitis of the perianal, perineal, and genital. Diagnosis can be established through clinical examination. Main principle of therapy is adequate resuscitation, parenteral antibiotic, and debridement. Urine and fecal diversion, hyperbaric treatment, and reconstructive surgery can improve the outcome. Some scoring system for diagnostic accuracy and mortality predictions are Laboratory Risk Indicator for Necrotizing Fasciitis Score (LRINEC) and Fournier Gangrene Severity Index (FGSI). Mortality rate is still high despite appropriate treatment. Management of Fournier’s gangrene in type C hospital was discussed.